2011
DOI: 10.1590/s1517-83822011000100040
|View full text |Cite
|
Sign up to set email alerts
|

Human T-Lymphotropic virus (HTLV) type I in vivo integration in oral keratinocytes

Abstract: Although the infection of HTLV-1 to cell components of the mouth have been previously reported, there was not until this report, a detailed study to show the characteristics of such infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…However, it remains to be determined whether those lymphocytes circulate for longer in saliva or are newly deposited in saliva and milk by leaking from microcirculation as has been reported previously (32)(33)(34)(35). There is some indirect evidence, both from our own study and previous work for HTLV-1 infection of oral mucosa by cellto-cell contact with circulating T cells, primarily through breast-feeding (32,(36)(37)(38).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…However, it remains to be determined whether those lymphocytes circulate for longer in saliva or are newly deposited in saliva and milk by leaking from microcirculation as has been reported previously (32)(33)(34)(35). There is some indirect evidence, both from our own study and previous work for HTLV-1 infection of oral mucosa by cellto-cell contact with circulating T cells, primarily through breast-feeding (32,(36)(37)(38).…”
Section: Discussionsupporting
confidence: 57%
“…Previous reports showed an association of the presence in HAM/TSP patients of free genomic HTLV-1 RNAs with an active production of sIgA in (31,32). Thus the differences recorded between HAM/TSP mothers and asymptomatic carriers in the mucosal associated response suggest that both immunological and cellular changes occur during progression to disease.…”
Section: Discussionmentioning
confidence: 85%
“…It worth to note that Gillet and Willems demonstrated absence of BLV DNA in breast cancer patient's DNA. HTLV-1 virus also had been found in the other type of cells in different nonhematological cancers [32]: (i) Endometrial adenocarcinoma in rabbits [33], (ii) Hepatocellular carcinoma (HCC) in patients with chronic HCV infection [34], (iii) Non-small cell lung cancer [35], (iv) Small cell lung cancer [36], (v) HTLV-1 is isolated from immortalized epithelial cells [31], and primary oral keratinocytes [37]. Also, it was shown that HTLV-1 increases risk of bronchioloalveolar carcinoma [38].…”
Section: Viral Proteins As Factors Affecting Specific Cancer Pathwaysmentioning
confidence: 99%